Analisis Implementasi Kebijakan Kompensasi Pegawai pada Badan Pusat Statistik Kabupaten Karawang - Wanda Pitaloka; Uus Mohammad Darul Fadli (Politeknik Kampar, 2024)
This research was carried out with the aim of understanding the impact of compensation on employee performance at the Karawang Regency Central Statistics Agency, that compensation has a positive effect on employee performance which is significant both individuals or groups in an organization/company. This research uses qualitative methods, this research was conducted at the Karawang Regency Central Statistics Agency (BPS Karawang) located on Jl. Cakradireja No.36, Nagasari, West Karawang, Karawang Regency, West Java 41315, Indonesia. The data source used is primary data source through interviews with predetermined informants. The data collection techniques used were interviews, observation and documentation. The results of the research show that the Karawang Regency Central Statistics Agency does not only provide compensation in the form of money, namely in the form of opportunities to increase career levels, take part in certain activities, become a resource person, become an instructor in training and so on. The conclusion of this research is that it is hoped that by implementing optimal employee compensation policies, employee performance and motivation at BPS Karawang Regency can be improved.